An Energy-Efficient Scheduling Strategy Based on Load Conditions in LTE System - Kai Wen; Yali Miao (Dianxin kexue)
The key question of green communication is how to reduce energy consumption while maintaining the quality of service. According to the conception of trading bandwidth for energy, with the addition of taking system throughput and fairness among users into consideration, a resource scheduling strategy based on system load conditions for LTE downlink was proposed to reduce energy consumption by improving energy efficiency at the cost of spectral efficiency. The simulation results show that the two algorithms can greatly reduce transmit power on the premise that the requirements of the user rate are met, and ensure the realization of the fairness among users.